WOMEN IN REPRODUCTIVE SCIENCE: To be or not to be a testis. Issue 6 (December 2019) - Capel, Blanche
Abstract : Work that established the testis as the driver of male development, and the Y chromosome as the bearer of the male-determining gene, established a working model, and set the stage for the molecular age of mammalian sex determination. The discovery and characterization of Sry / SRY at the top of the hierarchy in mammals launched the field in two major directions. The first was to identify the downstream transcription factors and other molecular players that drive the bifurcation of Sertoli and granulosa cell differentiation. The second major direction was to understand organogenesis of the early bipotential gonad, and how divergence of its two distinct morphogenetic pathways (testis and ovary) is regulated at the cellular level. This review will summarize the early discoveries soon after Sry was identified and focus on my study of the gonad as a model of organogenesis.